Come Together to Decrease Depression: Women's mental health, social capital, and participation in a Kenyan combined microfinance program. (September 2021) - Goodman, Michael L; Elliott, Aleisha J; Gitari, Stanley; Keiser, Philip; Onwuegbuchu, Erica; Michael, Nicole; Seidel, Sarah
Background: Tools and systems to improve mental health have been understudied in low-resource environments, such as sub-Saharan Africa. This study explores depression amongst women participating in a community-based intervention combining savings- and lending-groups, entrepreneurial training and other skills training. Aims: This study aims to determine whether depression decreases with more program participation, and the extent to which social capital variables may explain these changes. Method: Survey data were gathered in June 2018, within 6 months of group formation, and again in June 2019 from 400 women participants in the program. Data between 2018 and 2019 were compared using Wilcoxon rank-sum and Chi square tests. Inferential statistics included random effects regression models and general structural equation models. Results: At 1-year follow-up, depression and loneliness amongst Kenyan women ( n = 400) participating in the program had decreased. Social capital remained higher within groups than within the broader community, and mediated the association between program participation and decreased depression. Conclusions: Findings suggest this novel, community-based intervention has the potential to benefit mental health. Future research, including a randomised control trial, is required to establish (1) the extent of the program's benefits and (2) the program's application to particular subject areas and population segments.